2005
DOI: 10.1016/j.febslet.2005.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Tobamovirus‐resistant tobacco generated by RNA interference directed against host genes

Abstract: Two homologous Nicotiana tabacum genes NtTOM1 and NtTOM3 have been identified. These genes encode polypeptides with amino acid sequence similarity to Arabidopsis thaliana TOM1 and TOM3, which function in parallel to support tobamovirus multiplication. Simultaneous RNA interference against NtTOM1 and NtTOM3 in N. tabacum resulted in nearly complete inhibition of the multiplication of Tomato mosaic virus and other tobamoviruses, but did not affect plant growth or the ability of Cucumber mosaic virus to multiply.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 28 publications
(31 reference statements)
3
53
0
Order By: Relevance
“…NtCPIP2a and NtCPIP2b act as potyviral susceptibility factors during Potato virus Y infection and along with heat shock protein 70, they act as plant chaperones and are essential for virus movement (Hofius et al, 2007). TOM1 and TOM3 proteins in Arabidopsis and N. tabacum are associated with the multiplication of TMV and tobamoviruses (Asano et al, 2005;Yamanaka et al, 2000). Based on those results, we suspect that various host proteins can bind to viral RNAs and/or proteins of multiple plant viruses.…”
Section: Discussionmentioning
confidence: 93%
“…NtCPIP2a and NtCPIP2b act as potyviral susceptibility factors during Potato virus Y infection and along with heat shock protein 70, they act as plant chaperones and are essential for virus movement (Hofius et al, 2007). TOM1 and TOM3 proteins in Arabidopsis and N. tabacum are associated with the multiplication of TMV and tobamoviruses (Asano et al, 2005;Yamanaka et al, 2000). Based on those results, we suspect that various host proteins can bind to viral RNAs and/or proteins of multiple plant viruses.…”
Section: Discussionmentioning
confidence: 93%
“…Another translation factor, elongation factor1A (EF1a), interacts directly with the MT domain of the TMV 126-/183-kD proteins and is necessary for normal virus accumulation (Yamaji et al, 2006(Yamaji et al, , 2010. Other host factors such as membrane proteins encoded by the Tobamovirus multiplication (TOM) genes that interact with the 126-kD protein or its ortholog and an associated host GTPbinding protein, ARL8, are essential for tobamovirus replication in Arabidopsis (Arabidopsis thaliana) and N. tabacum (Yamanaka et al, 2000;Yamanaka et al, 2002;Asano et al, 2005;Nishikiori et al, 2011). Also, the tomato resistance gene, Tm-1, was shown to interact with the homologs of the 126-and 183-kD proteins from the tobamovirus Tomato mosaic virus to prevent its replication (Ishibashi et al, 2007).…”
mentioning
confidence: 99%
“…More recently, Hagiwara- Komoda et al (2008) reported that the 130-kDa protein of ToMV was detected in both a soluble and a crude membrane fraction. The latter contains the TOM1 protein, which is required for multiplication of tobamoviruses in Arabidopsis and tobacco (Asano et al 2005;Yamanaka et al 2000). In the NtTOM1 (tobacco ortholog of TOM1)-overexpressing transgenic tobacco plants, the level of the 130-kDa protein in the soluble fraction was reduced because the overexpressed NtTOM1 recruited and anchored the 130-kDa protein to membranes.…”
Section: Molecular and Biological Characterization Of Attenuated Virusesmentioning
confidence: 99%